VHDL modeling and simulation of the back-propagation algorithm and its mapping to the RM - Erdogan, S. S.; Abdul Rahman, Abdul Wahab; T., H. Hong (1993)
The Reconfigurable Machine (RM) is a parallel architecture that is built using Xilinx's 4005 Field Programmable Gate Array (FPGA) and associated fast SRAMs. In this study, VHDL modeling and simulation of a fully connected there-layer Back-Propagation (BP) is attempted with a view towards its mapping to a reconfigurable . parallel architecture. The mapping encompasses both the forward and backward passes. A bottom-up approach is used which starts from the configuration of processing elements to achieve effective computation of floating-point sum-of-products. The FPGAs perform the floating-point multiplication, addition and function evaluation, while the local SRAMs are used for storing U0 data for RM.